Motivations of parasuicide tendencies among young married females at Parirenyatwa Pychiatric Unit in Harare - Haruperi, Tendai (2017)
The study explored the motives of parasuicides tendencies among young married females who seek assistance at Parirenyatwa Psychiatric Unit. The numbers of parasuicide patients are increasing monthly in Harare and the majority are young females of the age of 16 to 22. There are very few studies done in Zimbabwe on motives behind parasuicide or self injuries as a way of attempting suicide especially in married adolescents females. The researcher reviewed literature from other scholars and very few researches address parasuicide just in general. The research adopted the exploratory research design to expose the causes of suicide attempts in young married females with a sample of 12 respondents selected using the opportunistic purposive sampling technique. The results of study indicated that financial crisis emanating from substance abuse, to get rid of painful situations, witchcraft accusations and evil spirit possession, family disunity and inter-conflicts, physical and verbal abuse by the husband and the in-laws. In conclusion the study realise that it is difficult for these young mothers to endure such perpetuating and precipitating factors so as to have positive perceived behaviour and attitude. It was recommended that the government must come up with a blue print on suicide prevention, family integration tolerance and reconciliation. The conflicting parties surrounding the victims that is the spouses, siblings, parents and the inlaws should unite, seek psycho-social advice and family psychotherapy to save the life of vulnerable young married females